2014
DOI: 10.1101/005322
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adaptation to a novel predator inDrosophila melanogaster: How well are we able to predict evolutionary responses?

Abstract: Evolutionary theory is sufficiently well developed to allow for short-term prediction of 2 evolutionary trajectories. In addition to the presence of heritable variation, prediction requires knowledge of the form of natural selection on relevant traits. While many studies 4 estimate the form of natural selection, few examine the degree to which traits evolve in the predicted direction. In this study we examine the form of natural selection imposed 6 by mantid predation on wing size and shape in the fruitfly, Dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 86 publications
0
1
0
Order By: Relevance
“…Adaptive responses to predation risk may be modified by other stressors, as environmental stress can increase the costs (Hanazato, ; Huber et al ., ; Teplitsky et al ., ) or decrease investment in defences (Barry, ; Relyea, ; Teplitsky et al ., ). A few studies have tested for heritability in predator avoidance traits and usually found substantial genetic variation (Grant & Mettler, ; Stirling et al ., ; Relyea, ; Brokordt et al ., ; DeNieu et al ., ; but see Blumstein et al ., ). Whether predator avoidance is genetically correlated with other types of stress resistance is largely unknown (but see Jansen et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Adaptive responses to predation risk may be modified by other stressors, as environmental stress can increase the costs (Hanazato, ; Huber et al ., ; Teplitsky et al ., ) or decrease investment in defences (Barry, ; Relyea, ; Teplitsky et al ., ). A few studies have tested for heritability in predator avoidance traits and usually found substantial genetic variation (Grant & Mettler, ; Stirling et al ., ; Relyea, ; Brokordt et al ., ; DeNieu et al ., ; but see Blumstein et al ., ). Whether predator avoidance is genetically correlated with other types of stress resistance is largely unknown (but see Jansen et al ., ).…”
Section: Introductionmentioning
confidence: 99%